Implication of Coal Mining Permit Governance to Environmental Degradation in East Kalimantan - Mohamad Nasir (Faculty of Law, Mulawarman University, 2022)
This article analyzes the regulation dynamics regarding coal mining permit governance and its impact on environmental degradation. This paper addresses two main issues. First, it explores the dynamics of coal mining regulations and to what extent they create legal uncertainty in coal mining permit governance. Second, it investigates the implications of the legal uncertainty to the environmental damage around the mining sites. The findings demonstrate that two factors have driven policies and laws in the coal mining sector for over a decade. First, coal mining legislation relates to other industries such as the environment, forestry, spatial planning, and regional governance. Besides, the regulations are multi-level, where the authority lies with the central, provincial, and district/city governments. The second is legislative capture, where licensing legal norms are